Prognostic Models for Patients With Gleason Score 9 Prostate Cancer: A Population-Based Study - Qiu, Jianhui; Cai, Desheng; Wang, Zixin; Zhou, Jingcheng; Gong, Yanqing; Cai, Lin; Gong, Kan (Frontiers in Oncology, 2021)
Purpose: Gleason score (GS) system is one of the most widely used histological grading methods for prostate cancer (PCa) all over the world. GS can be obtained by adding the primary Gleason pattern (GP) and secondary GP. Different proportions of GP 4 and GP 5 in prostate specimens can both lead to GS 9. In this study, we explored whether GP 5+4 or GP 4+5 were associated with different prognoses among patients with GS 9 PCa. Materials and methods: A retrospective population-based study was conducted on 10124 subjects diagnosed with GS 9 PCa between 2004 and 2009 from the Surveillance, Epidemiology, and End Results program. A 1:1 propensity-score matching (PSM) was performed to balance baseline characteristics between the GP 4+5 and 5+4 groups and to compare prognoses between the two groups. Cox regression analysis and Fine-Gray competing risk regression models were adopted to screen the covariates significantly associated with all-cause mortality (ACM) and cancer-specific mortality (CAM). Results: GP 5+4 was associated with higher risks of ACM and CSM before or after PSM than GP 4+5. In the original cohort, there were eight independent predictors for ACM, which were age at diagnosis, race, AJCC NM stage, PSA levels, treatments, GP and marital status, confirmed by Cox analysis and nine independent predictors for CSM, which were age at diagnosis, race, AJCC TNM stage, PSA levels, treatments, GP and marital status, confirmed by the competing-risk model. Conclusion: GP 5+4 was associated with poorer overall survival and cancer-specific survival compared with GP 4+5.